On the state of the knowledge of rainfall extremes in the western and northern Pacific basin1. (25th March 2014) - Kruk, Michael C.; Lorrey, Andrew M.; Griffiths, Georgina M.; Lander, Mark; Gibney, Ethan J.; Diamond, Howard J.; Marra, John J.
ABSTRACT The relevant literature on extreme rainfall events in the Pacific remains relatively sparse compared to other regions (e.g. the coterminous United States, Europe, etc.). Moreover, several recent reports on climate in the Pacific mention the paucity of extremes information and often list 'trends in historical climate' as a necessary next step. This scientific assessment meets this need by examining historical trends in and drivers of extreme rainfall events across the entire Pacific Basin, inclusive from Alaska southward to Australia, and longitudinally from the Philippines eastward to North America, with an emphasis on island and coastal locations (within 200 km of the coastline). There is evidence of a general decrease in the frequency of annual extreme rainfall events, yet the amount of extreme precipitation contributing to annual and seasonal totals appears to be on the rise. Region‐wide, the number of consecutive dry days is increasing for those locations that are already dry, while the number of consecutive wet days is increasing for the already wet locales. The data for extreme rainfall statistics are considered to be relatively high quality for trend detection, while the level of understanding of the physical causes behind extreme rainfall is positively high. Since the ability to analyze the changes in historical rainfall extremes with some confidence is relatively recent, understanding is expected to improve in the future with the advancement of new datasets and 'climate reanalysis' projects.